2009
DOI: 10.1139/g09-001
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide analysis of rice (Oryza sativa L. subsp. japonica) TATA box and Y Patch promoter elements

Abstract: The TATA box is one of the best characterized transcription factor binding sites. However, it is not a ubiquitous element of core promoters, and other sequence motifs such as Y Patches seem to play a major role in plants. Here, we present a first genome-wide computational analysis of the TATA box and Y Patch distribution in rice (Oryza sativa L. subsp. japonica) promoter sequences. Utilizing a probabilistic sequence model, we ascertain that only approximately 19% of rice genes possess the TATA box, but approxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
26
0
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(35 citation statements)
references
References 14 publications
5
26
0
2
Order By: Relevance
“…The selected pHsp18 and pHsp82 promoter fragments retained the essential elements to drive heat shock induction in these tissues, and they performed as expected in GM plants. This is in agreement with previous publications where regulatory elements including the TATA box were in silico predicted in the two 5′ proximal regions [65], [66].…”
Section: Discussionsupporting
confidence: 93%
“…The selected pHsp18 and pHsp82 promoter fragments retained the essential elements to drive heat shock induction in these tissues, and they performed as expected in GM plants. This is in agreement with previous publications where regulatory elements including the TATA box were in silico predicted in the two 5′ proximal regions [65], [66].…”
Section: Discussionsupporting
confidence: 93%
“…To identify sequence elements that show TFBS enrichment, we next searched the promoters for specific upstream locations where these TFBS elements could be collectively enriched (see Methods: 3PEAT TSS Peak Prediction Model). We used a standard log-likelihood TFBS scanning technique to approximate DNA binding affinity along with a set of 200 known plant elements characterized in the literature (Grasser, 2006;Megraw et al, 2006;Bryne et al, 2008;Wingender, 2008;Civán and Svec, 2009;Yamamoto et al, 2009).…”
Section: The Location Of Transcription Initiation Can Be Accurately Mmentioning
confidence: 99%
“…To identify regions where transcription factor binding sequences are enriched with respect to the TSS, we started with a set of 203 TF positional weight matrices (PWMs) collected from a variety of sources (Grasser, 2006;Megraw et al, 2006;Bryne et al, 2008;Wingender, 2008;Civán and Svec, 2009;Yamamoto et al, 2009). While the PWMs used in this study were derived using experimentally supported data (rather than strictly computational approaches), PWMs are rarely a perfect characterization of TF binding domains or their sequence specificity.…”
Section: Peat Model Constructionmentioning
confidence: 99%
“…While many of these CPEs have been well studied in animals, studies in plants are not as extensive, leaving many elements that have only been identified computationally (Yamamoto et al, 2007a(Yamamoto et al, , 2011Civán and Svec, 2009;Bernard et al, 2010;Zuo and Li, 2011;Kumari and Ware, 2013). This is especially problematic considering that even some of the most well studied and conserved elements such as TATA and Inr show distinct consensus sequence differences in plants compared with their yeast and mammalian counterparts, making plant-specific consensus sequence identification an important priority in accurate promoter identification in plants (Kumari and Ware, 2013).…”
Section: The State Of the Core: Our Limited Knowledge Of Pol II Core mentioning
confidence: 99%